Dry Lab – Laboratorium Virtual Untuk Anlisa Rekayasa Lumpur Pemboran - M. Mahlil Nasution; Edy Soesanto; Aly Rasyid (Jurnal Bhara Petro Energi, 2022)
Dry Lab is a virtual laboratory design, also called as a laboratory of the future. Dry Lab was designed because of the increasingly advanced computerized especially Artificial Intelligence for making a simulator that can function to simulate a tool wich is can similiar with the real condition so that it gets the same results as when run in a conventional laboratory. With the existence of this Simulator technology, then I try to make a virtual simulator for drilling mud analysis which is very much needed in the world of oil engineering education especially and also needed in the world of oil and gas industry, especially when conducting drilling activities.